Food and agricultural wastes as substrates for bioelectrochemical system (BES): The synchronized recovery of sustainable energy and waste treatment. (July 2015) - ElMekawy, Ahmed; Srikanth, Sandipam; Bajracharya, Suman; Hegab, Hanaa M.; Nigam, Poonam Singh; Singh, Anoop; Mohan, S. Venkata; Pant, Deepak
Abstract: Bioelectrochemical systems (BESs) are one of the recent promising technologies developed for their multi-faceted applications such as bioenergy generation, wastewater treatment and synthesis of value added chemicals. Among these applications, microbial fuel cells (MFCs) for wastewater treatment with simultaneous power generation are being widely studied, while the other applications are gaining prominence very recently. A wide range of wastewaters, ranging from domestic to industrial origin, were studied for their potential of power generation in MFCs with their simultaneous treatment. Though, some reviews have been published in the direction of consolidating the data of different wastewaters used as substrates in MFC, detailed review pertaining to the food and agriculture based wastewater was not yet reported. Considering the hidden potential of food and agricultural wastewater, this review article provides a comprehensive view on the MFC research related to these types wastewater. Major bottlenecks in enhancing the power output and treatment efficiencies along with the future directions were also discussed. Highlights: Electro-biotechnological basics of BES are discussed in detail. Problems related to the food and agricultural wastes across the globe are reported. Existing treatment methodologies for food and agricultural wastes are mentioned. Most of the reported MFC studies in this area are consolidated. Major bottlenecks in enhancing the process efficiency are discussed.